Population-based study of amyotrophic lateral sclerosis and occupational lead exposure in Denmark - Dickerson, Aisha S (Occup Environ Med, 2019)
OBJECTIVES: Previous research has indicated links between lead (Pb) exposure and increased risk of neurodegenerative disorders, including amyotrophic lateral sclerosis (ALS). in this study, we evaluated the association between occupational Pb exposures and ALS. METHODS: ALS cases were ascertained through the Danish National Patient Registry from 1982 to 2013 and age and sex-matched to 100 controls. Using complete employment history since 1964 from the Danish Pension Fund, cumulative Pb exposure was estimated for each subject via a Danish job exposure matrix. Associations were evaluated using conditional logistic regression analyses and stratified by sex. RESULTS: For men with >50% probability of exposure, there was an increase in odds of ALS for exposures in the 60th percentile or higher during any time 5 years prior to diagnosis (aOR: 1.35; 95% Ci 1.04 to 1.76) and 10 years prior to diagnosis (aOR: 1.33; 95% Ci 1.03 to 1.72). No significant associations were observed in women, and there were no linear trends seen for Pb exposures for either sex. CONCLUSIONS: Our study indicates an association between consistently higher occupational Pb exposures and ALS. These findings support those of previously reported associations between ALS and specific occupations that commonly experience Pb exposure.